Letter - Harris, Oliver
011-0034-001 Telephone No 4869. South Wales Miners Federation OLIVER HARRIS, GENERAL SECRETARY. 2 St. Andrew's Crescent. Cardiff. 20th October, 1937 Sir Walter Citrine, Trades Union Congress Transport House, Smith Square, London, SW1 Dear Sir Walter, A request has been made by a representative of the Spanish Government on behalf of the Asturian miners that the British and French Governments should assist in an attempt to secure the evacuation of the Miners from Asturias. It is stated that as the Spanish Government are unable to render any assistance to the Asturian people in their fight against Franco their position is desperate and ultimately they must succumb to the attacks of the rebels. It is reported that Franco does not take any prisoners from amongst the Asturian miners,but that wounded and prisoners are slaughtered without mercy. If this is true we think that every effort should be made to get the British and French Governments to comply with the request of the representative of the Spanish Government, and render such assistance as is necessary to secure the evacuation of the Asturian miners. My Council therefore urges the Trades Union Congress to make representations to the British Government for that purpose. Yours faithfully, [Oliver Harris] 292/946/11/34